Social influence in persuasion and negotiation: a hyperscanning EEG and autonomic measures study - Balconi, Michela; Rovelli, Katia; Angioletti, Laura (Frontiers in Neuroscience, 2025)
Effective negotiation relies on integrating diverse perspectives to reach a common resolution. While previous research examined the neural and autonomic underpinnings of persuasion and negotiation separately, little is known about how prior persuasive roles influence subsequent negotiation dynamics. This study employs a hyperscanning electrophysiological (EEG) and autonomic recording paradigm to investigate whether central and autonomic activity vary depending on the negotiation stages and the speaker-listener role. Participants first engaged in a Persuasion Phase (PP), assuming either the role of persuader or receiver, before transitioning to a collaborative Negotiation Phase (NP), in which they had symmetrical roles (as member 1 and member 2) and interacted across three negotiation stages: the Stage of Personal Declaration (SPD); the Stage of Interactive Negotiation (SIN); the Stage of Consensus Finalization (SCF). Results revealed significant EEG modulations across negotiation stages, with delta and theta oscillations in the left frontal region reflecting cognitive monitoring and social decision-making processes during the SCF. Alpha activity suggests a more passive role for members 1 (former persuaders) in the SCF, while members 2 spoke, with increased beta power indicating cognitive control and social engagement during this stage. Also, gamma oscillations showed different activations for distinct roles highlighting cognitive integration of perspectives and arguments during the three negotiation stages. Finally, autonomic data showed heightened SCL activation in the SPD for members 1 when members 2 spoke, signaling increased arousal when encountering counterarguments. These findings provide novel insights into the neural and autonomic correlates of negotiation, emphasizing the impact of prior persuasive experiences.